Fordham University School of Law : a history - Kaczorowski, Robert J. (Fordham University Press, 2012)
Tracing Fordham Law School's history in the context of developments in legal education over the course of the 20th century, this book pinpoints those factors that produce greatness in a law school and those that contribute to its decline. Kaczorowski traces how the Law School, with the unprecedented financial support and active involvement of its alumni, is resuming its prior position as one of America's leading law schools.